CULTURALLY RESPONSIVE TEACHING PRACTICES AND THEIR EFFECTS ON MINORITY STUDENT ACHIEVEMENT: A SYSTEMATIC REVIEW OF THE LITERATURE - Nuraedah Nuraedah; Al-Amin (Adisam Publisher, 2025)
This systematic literature review investigates the effect of Culturally Responsive Teaching Practices (CTRP) on minority students' academic achievement, engagement, and social-emotional well-being. By analysing existing research, this study reveals that the implementation of CTRP, which involves acknowledging students' cultural identities, incorporating diverse perspectives into the curriculum, and adapting instruction, significantly improves educational outcomes for culturally marginalised students. However, the success of CTRP depends on teachers' cultural competence, institutional support and availability of resources. This study highlights the need for further efforts in teacher training, curriculum development and research to advance the understanding and implementation of CTRP, with the ultimate goal of closing the achievement gap and promoting equity in education for all students, regardless of their background. The findings provide valuable insights for education practitioners, policymakers and researchers who seek to create more inclusive and diversity- supportive learning environments.